Enhancing empathy of medical students in clinical training: a narrative-driven virtual reality experience for understanding undiagnosed chronic pain - Xu, Wenjie; Yang, Xuesong (Frontiers in Virtual Reality, 2025)
ObjectivesChronic pain, particularly when undiagnosed, is often misunderstood by clinicians due to its invisible and subjective nature. This study aimed to design and evaluate a narrative-driven Virtual Reality (VR) experience that immerses medical students in the fragmented reality of a patient living with undiagnosed chronic pain. The project seeks to bridge the empathy gap in clinical training for medical students and healthcare professionals while enhancing understanding of patient experiences.MethodsWe developed a 4-minute immersive VR experience. Seventy undergraduate medical and health professional students with prior clinical exposure to chronic pain patients participated in the study. Following the experience, participants completed two questionnaires: one assessed the usability and validity of the VR application, while the other evaluated the medical students’ empathy and learning outcomes through a comparative analysis of post-experience surveys.ResultsThe SUS score was 70.13 ± 7.38, suggesting an above-average evaluation of the system’s usability and maturity. VR-experienced participants showed significantly better comprehension of chronic pain’s daily impacts and stronger emotional resonance with patient suffering. Additionally, the students in VR-experienced group rated the tool higher for its effectiveness in fostering empathy and improving knowledge retention.ConclusionOverall, the VR experience achieved the expected outcomes, with students identifying it as an immersive and impactful educational tool. It holds promise for enhancing empathy in clinical training, such as regarding undiagnosed chronic pain, potentially improving diagnosis and treatment approaches. While the results underscore VR’s potential to humanize chronic pain education, future studies should include longitudinal assessments, expanded narratives that reflect diverse patient experiences, and opportunities for users to engage with multiple scenarios, thereby better representing the full spectrum of challenges in many diseases.